Liberalization of Trade in Financial Services and Financial Sector Stability (Empirical Approach) - Kireyev, Alexei (IMF Working Papers; Working Paper ;, 2002)
The paper explores empirically the links between the WTO-driven liberalization of trade in financial services and the stability of national financial systems. Econometric testing of indicators intended to proxy financial sector stability-subdivided into exchange rate and banking sector stability-suggests that opening of the financial sector is an efficient policy instrument at the disposal of the authorities for achieving a variety of macroeconomic goals. While liberalization is found to be broadly conducive to stability, the outcome of liberalization on exchange rate stability is less predictable than on banking sector stability.